Coaxial Electrospinning of PCL-PVA Membranes Loaded with N-Heterocyclic Gold Complex for Antitumoral Applications - Raffaele Longo; Luigi Vertuccio; Francesca Aliberti; Annaluisa Mariconda; Marialuigia Raimondo; Pasquale Longo; Liberata Guadagno (Fibers)
Coaxial electrospun membranes made of polycaprolactone (PCL) and polyvinylalcohol (PVA) were produced and filled with a promising synthetic gold complex (AuM1) for antitumoral applications. Coaxial nanofibers characterized by a PVA shell and PCL + AuM1 core were made to design a multi-step release in a physiological environment. The coaxial structure can sensitively limit the burst effect, allowing the release of 90% of the active substance AuM1 in about three days. By comparison, the PCL membrane loaded with AuM1 produced via uniaxial electrospinning releases 90% of the drug in about 1 h. The correlation of release kinetic data with the morphological evolution and the spectroscopic investigation highlighted how coaxial electrospinning is a promising process for designing drug delivery systems to control the release of active substances over time. The proper design of core–shell systems could be of great interest for prolonged therapies, such as antitumoral therapy.